Simultaneous Gastric and Ileal Trichobezoars Causing Small Bowel Obstruction: A Case report - Lal, S; Shukla, P; Yedalvar, V; Shrivastava, GP (Journal of Nepal Paediatric Society, 2011)
The corrected PDF for this article was loaded on 07/02/2011. Bezoars are conglomerates of food or fiber in the alimentary tract of humans and certain animals, mainly ruminants. A trichobezoar represents a mass of accumulated hair. Trichobezoars may present as an isolated gastric mass, as an extension into the small intestine, or as an independent fragmented mass in the small intestine. The presence of discrete coexisting gastric and ileal trichobezoars has been reported only rarely in the literature. This is a case report of a 10-year-old girl presenting with small-bowel obstruction secondary to synchronous trichobezoars in the stomach and ileum. The case highlights the role of imaging and importance of complete evaluation of the gastrointestinal tract at the time of surgical evacuation. Key words: Trichobezoars; stomach; small bowel; obstructions DOI: 10.3126/jnps.v31i1.3968 J Nep Paedtr Soc 2010;31(1):72-74